المشكلات الإنتاجية والتسويقية التي تواجه مزارعي النخيل في الأردن - الطاهات، إبراهيم سليمان; الطراونة، محمد سالم (جامعة الملك فيصل, 2018)
Palm cultivation in Jordan is relatively new and have seen significant expansion. This is due to suitab climate, investment conditions, and the application of income diversification policies in Jordan. The purpose of this work is to explore the problems confronting palm trees farmers in Jordan and measure the degree of their concern with these problems. In addition, it aimed to analyze the economic and social characteristics of the farmers throughout a questionnaire distributed to 57 farmers. The questionnaire included a scale of 27 sections with its first section covering general information including age, qualification, experience, and the farmland area. Five points Likert Scale was used to measure the response of the farmers to the problems. Reliability and consistency of the study tool was evaluated by a group of expert doctors in agriculture. Reliability test alpha coefficient was 0.79. The results showed that interest rate on agricultural loans is the most important problem followed by obtaining agricultural loan. The least important problem was the inadequacy of market places. The results also showed the existence of a significant relation between personal characteristic with the importance and degree of problems affecting farmers of palm trees in Jordan at a significant level P<0.05. The study thus recommends facilitating measures and overcoming the procedural obstacles of obtaining agricultural loans for farmers.
تعد زراعة النخيل في الأردن من الزراعات الحديثة، وقد شهدت انتشارا واسعا؛ وذلك لتوافر الظروف المناخية والاستثمارية لها. وتكريسا لمبدأ تنويع مصادر الدخل لدى المزارعين، أتت هذه الدراسة بهدف البحث في المشكلات الإنتاجية والتسويقية التي تواجه مزارعي النخيل في الأردن، وقياس درجة توجههم نحوها، إضافة إلى تحليل العلاقة بين درجة التوجه وبعض الخصائص الاقتصادية والاجتماعية للمزارعين من خلال استبانة وزعت على (57) مزارعا، وقد تضمنت الاستبانة مقياسا من (27) فقرة اشتمل الجزء الأول منها على معلومات عامة تتصل بخصائص عينة الدراسة تناولت: العمر، المؤهل العلمي، الخبرة، مساحة الحيازة. وقد استخدم مقياس ليكرت خماسي التدريج لقياس اتجاهات المبحوثين نحو المشكلات. فيما يتعلق بصدق وثبات أداة الدراسة، تم عرض الاستبانة على مجموعة من الأساتذة المتخصصين في الزراعة، واستخدم اختبار الثبات Reliability Test؛ حيث بلغت قيمة معامل ألفا (0.79). أظهرت النتائج أن مشكلة أسعار الفائدة المطبقة على القروض الزراعية هي الأكثر أهمية، يليها الحصول على قرض زراعي، وكانت آخر مشكلة من حيث الأهمية مشكلة كفاءة أماكن التسويق، كما أظهرت النتائج وجود علاقة معنوية بين الخصائص الشخصية وأهمية ودرجة تأثير المشكلات التي تواجه مزارعي النخيل في الأردن عند مستوى معنوية P < 0.05. توصي الدراسة بضرورة تسهيل حصول المزارعين على القروض.
Keywords: النخيل -- الإنتاج الزراعي -- التسويق الزراعي -- الأردن